2009
DOI: 10.1186/1471-2172-10-10
|View full text |Cite
|
Sign up to set email alerts
|

ER stress affects processing of MHC class I-associated peptides

Abstract: Background: Viral infection and neoplastic transformation trigger endoplasmic reticulum (ER) stress. Thus, a large proportion of the cells that must be recognized by the immune system are stressed cells. Cells respond to ER stress by launching the unfolded protein response (UPR). The UPR regulates the two key processes that control major histocompatibility complex class I (MHC I)-peptide presentation: protein synthesis and degradation. We therefore asked whether and how the UPR impinges on MHC I-peptide presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 73 publications
3
87
1
1
Order By: Relevance
“…Exposure to ER stress conditions cells for survival, decreases levels of HLA class I proteins at the cell surface and decreases the synthesis of new HLA class I molecules. This prepares cells for subsequent, more severe stress (40,48). We show evidence of the regulation of ERp57 at the cellular level by the amounts of glucose in the medium.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Exposure to ER stress conditions cells for survival, decreases levels of HLA class I proteins at the cell surface and decreases the synthesis of new HLA class I molecules. This prepares cells for subsequent, more severe stress (40,48). We show evidence of the regulation of ERp57 at the cellular level by the amounts of glucose in the medium.…”
Section: Discussionmentioning
confidence: 63%
“…The role of ERp57 in the folding and assembly of HLA class I molecules has been reported (39,40). Therefore, we studied which HLA class I molecules and/or subunits of the antigenprocessing machinery (APM) could be affected by ERp57 expression and whether the processing machinery might be involved.…”
Section: Identification Of Bone Metastatic Candidatementioning
confidence: 99%
“…We showed that, although B cells mounting an UPR following accumulation of a KDEL-retained protein in the ER upregulate MHC class II and costimulatory molecules (72), they present decreased levels of high-affinity peptide complexed to MHC class II. Similarly, mouse thymoma cells under palmitate or glucose deprivation-induced ER stress decrease transgenic OVA Ag presentation on MHC class I (73). These findings begin to suggest that APC under ER stress undergo remodeling of the processing machinery, yielding decreased presentation of high-affinity immunodominant peptides and increased presentation of subdominant or low-affinity peptides.…”
Section: The Upr Intersects With Cellular Proinflammationmentioning
confidence: 87%
“…Evidence also suggests that the UPR may blunt the antitumor immune response by affecting antigen presentation and antigen-presenting cells per se. Perturbation of the secretory pathway or ER stress decreases the presentation of high-affinity peptides by major histocompatibility complex (MHC) classes I and II (120,121). Moreover, UPR-dependent products that transfer from cancer cells to DCs trigger arginase activation (an enzyme that suppresses T cell function) (122) and hinder the ability of DCs to cross-present antigen and cross-prime CD8 + T cells (119).…”
Section: Er Proteostasis Control In Glioma Stromal Cells Gliomas Reprmentioning
confidence: 99%